Monetary policy and the run risk of loan funds - Nicola Cetorelli; Gabriele La Spada; Jo\~ao A. C. Santos (Federal Reserve Bank of New York, 2022)
Loan funds are open-end mutual funds holding predominantly corporate leveraged loans. We document empirically that loan funds are significantly more susceptible to run risk than any other category of debt funds, including corporate bond funds. Most importantly, we establish a link between loan funds' flows and monetary policy, based on the institutional characteristics of their portfolio holdings. We find robust evidence indicating a pro-cyclical relationship between monetary policy and loan-fund flows. This relationship, however, is asymmetric: weaker for policy-rate increases and stronger for policy-rate decreases. Finally, the effect of monetary policy shocks on loan-fund flows also depends on the level of market short-term rates, suggesting that it is not only the direction of the monetary policy change that matters, but also the level of the policy rate at the time of the change. Our results thus identify a novel channel of monetary policy transmission affecting a critical segment of the credit sector, represented by leveraged lending.
Keywords: G23; E52; G28; 330; mutual funds; monetary policy; leverage lending